Towards the Issue of Kazakhstan Economy Decarbonization - Aubakirova, G.M.; Rudko, G.I.; Issatayeva, F.M.; Mazhitova, S.K. (BUKETOV BUSINESS REVIEW, 2022)
Object: To identify the features of building the decarbonized economy of Kazakhstan in the context of approaching countries with sustainable development. Methods: A systematic approach, a retrospective and comparative assessment. Results: The main approaches to the economy of Kazakhstan decarbonization in accordance with the international practice and the adopted long-term strategy for low-carbon development of the country were analyzed. The socioeconomic and institutional conditions of low-carbon development impact on selecting the key instruments for transforming the economy was shown. Conclusions: The analysis results demonstrate that implementing the institutional measures aimed at stimulating decarbonization in the medium and long term will accelerate the overcoming of barriers for industrial enterprises for transition to renewable energy and energy efficiency. Institutional transformations will deepen coordinated cooperation in the new energy era of the state, business and enterprise as equal partners.